Мikroirrigation oil-bearing plants in different climatic zones of Crimea (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The comparative study of growth and efficiency of Nepeta cataria var. citriodora Dum. and Elsholtzia stauntonii Benth. on subirrigation in a Steppe zone and Southern coast of Crimea is given.
Keywords: Nepeta cataria var. citriodora, Elsholzia stauntonii, Steppe zone Crimea.